2006
DOI: 10.1007/s10935-005-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Participation in “Parents Who Care”: Predicting Program Initiation and Exposure in Two Different Program Formats

Abstract: Predictors of participation and exposure across two formats of a universal prevention program are examined here. Families of 225 8th-grade students, balanced by race (African American and European American) and gender, were assigned to a parent and adolescent group format (PAG) or a self-administered format (SA). Logistic regression showed greater program initiation in SA than in PAG. Hierarchical regression showed only one variable (parent high-risk behavior) to be associated with lower program exposure in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 29 publications
3
55
0
1
Order By: Relevance
“…The results of multiple regression analyses supported the first hypothesis, and confirmed that child, parent, sociodemographic, and program variables were significantly related to PIP. The results seem to be consistent with the literature in terms of multiple contributors to prediction of parental intention (see Coatsworth et al 2006;Haggerty et al 2006;Heinrichs et al 2005;Littell and Tajima 2000;Spoth and Redmond 2000). Treatment participation appeared as a multifaceted phenomenon that is affected by multiple variables (Littell and Tajima).…”
Section: Discussionsupporting
confidence: 89%
“…The results of multiple regression analyses supported the first hypothesis, and confirmed that child, parent, sociodemographic, and program variables were significantly related to PIP. The results seem to be consistent with the literature in terms of multiple contributors to prediction of parental intention (see Coatsworth et al 2006;Haggerty et al 2006;Heinrichs et al 2005;Littell and Tajima 2000;Spoth and Redmond 2000). Treatment participation appeared as a multifaceted phenomenon that is affected by multiple variables (Littell and Tajima).…”
Section: Discussionsupporting
confidence: 89%
“…Often reported predictors of parental attendance include sociodemographic variables such as education and income level, which may be related to resources and ability to attend. [117][118][119][120] A future trial might consider providing parents with incentives in order to attend, including funds for travel or child-minding.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a self-administered format compared to a group format produced higher participation rates (Haggerty et al 2006) factors mediating the transfer of improved parenting into the parent-child relationship need to be clarified in future trials. The lack of consistent differences between Levels could also be due to an interaction with other characteristics which we could not analyze.…”
Section: Triple P Level and Delivery Formatmentioning
confidence: 99%